Students' learning styles and their effects on the use of social media technology for learning - Balakrishnan, Vimala; Gan, C.L. (Elsevier, 2016)
Students with different learning styles approach learning differently. With the rise of social media technologies, investigating the effect of these styles on their intentions to use social media for learning has become all the more important. This study explored the factors affecting students' intentions to use social media for learning based on their learning styles (i.e., participatory, collaborative, and independent), using the social media acceptance model. By convenience sampling, 300 Malaysian students were recruited via an online survey (Nparticipatory = 116; Nindependent = 97; and Ncollaborative = 87). The survey was prepared by drawing on the social media acceptance model. It was piloted before the final data collection step was conducted in August 2013. The demographic details of the students were analyzed using Statistical Program for Social Sciences 21, while path modeling and multivariate analyses were conducted using SmartPLS 2.0. The results revealed the significant effect of Self and Performance on students' intentions to use social media regardless of their learning styles. A pair-wise comparison revealed that Self was more significant in participatory students than in collaborative students. Effort was found to be the least significant factor, indicating the popularity of social media among students. Further insight into the different factors that drive students with different learning styles to use social media will help educators use this technology to assist learning more effectively.